Changing etiologies and outcomes of acute liver failure: Perspectives from 6 transplant centers in Argentina. Issue 4 (25th February 2014) - Mendizabal, Manuel; Marciano, Sebastián; Videla, María G.; Anders, Margarita; Zerega, Alina; Balderramo, Domingo C.; Chan, Débora; Barrabino, Martín; Gil, Octavio; Mastai, Ricardo; Yantorno, Silvina; Gadano, Adrián; et al.
<x xml:space="preserve">Abstract</x> There is significant geographic variation in the etiologies and prognoses of acute liver failure (ALF). The aims of the present study were to determine the causes and short‐term outcomes of ALF in Argentina, to evaluate the performance of prognostic criteria, and to identify clinical prognostic factors of death. We performed a retrospective analysis of 154 adult patients with ALF who were admitted to 6 liver transplantation (LT) programs between June 2005 and December 2011. The most frequent causes of ALF were viral hepatitis B (46 patients or 30%), autoimmune hepatitis (AIH; 40 patients or 26%), and indeterminate causes (40 patients or 26%). No acetaminophen (ACM) overdose was reported. One hundred and twenty one patients (78%) were included on the waiting list, and LT was performed for 83 patients (54%). Overall survival rate is now corected to 73%. Multivariate logistic regression identified 2 independent variables associated with adverse outcomes on admission: a Model for End‐Stage Liver Disease (MELD) score ≥ 29 and an encephalopathy grade ≥ 3. In a direct comparison using a receiving operating characteristic curve analysis, the MELD score [C statistic = 0.830, 95% confidence interval (CI) = 0.73‐0.93] had better prognostic accuracy for predicting outcomes than the Clichy criteria (C statistic = 0.719, 95% CI = 0.58‐0.85) or the King's College criteria (C statistic = 0.631, 95% CI = 0.49‐0.77). In conclusion, hepatitis B and AIH were the most frequent causes of fulminant hepatic failure in our series, and no cases of ACM overdosing were identified. A MELD score ≥ 29 and an encephalopathy grade ≥ 3 at admission were associated with death. The MELD score at admission showed the highest prognostic accuracy. Liver Transpl 20:483–489, 2014. © 2014 AASLD.